What determines productivity level in the long run? Evidence from Italians regions - Raffaello Bronzini; Paolo Piselli (European Regional Science Association (ERSA), 2005)
In this paper we estimate the long-run relationship between total factor productivity, R&D capital stock and human capital in the Italian regions between 1980 and 2001. We exploit recent developments of panel cointegration techniques to estimate the cointegration relationship, allowing for endogeneity and heterogeneity of regional cointegration vectors. The evidence shows that there exists a long-run equilibrium among the variables and that human capital elasticity is larger than R&D elasticity. Conditioned on the long-run equilibrium, we set out an Error Correction Model of TFP growth. In this framework, we test for exogeneity of TFP determinants, by carrying out Granger-causality tests. Our findings show that human capital is exogenously generated out of the model, while TFP and R&D are simultaneously determined.
Keywords: 330